3-D snake for US in margin evaluation for malignant breast tumor excision using mammotome. - Ruey-Feng Chang
The goal of this paper is to use the three-dimensional (3-D) snake technique in 3-D ultrasound to obtain the tumor contour for the pre- and the post-operative malignant breast excision by the vacuum assisted biopsy instrument Mammotome. This technique of assessing the margin of two can help the physician to evaluate the effect of the surgery. By using the anisotropic diffusion filter, the noise and speckles can be reduced. Then the stick detection is adopted for enhancing the edge. Finally, the gradient vector flow (GVF) snake is used to obtain the tumor contour. These techniques are extended to the 3-D techniques to increase the accuracy and robust of segmentation results. We hope that this study can help physicians to improve the minimal invasive operation for a breast tumor.
Keywords: 3D snake; 3D ultrasound; Anisotropic diffusion filter; Breast tumor; Gradient vector flow; Malignant breast tumor excision; Mammotome; Margin evaluation; Noise; Segmentation; Speckles; Surgery; Three-dimensional snake; Vacuum assisted biopsy instrument